Software engineering - Ian Sommerville (Addison-Wesley, 1995)
The book discusses a comprehensive spectrum of software engineering techniques and shows how they can be applied in practical software projects. Features of this book include: Computer-based, systems engineering, requirements analysis, architectural design, managing people, quality management, process improvement, software, re-engineering, CASE, software management, software evolution